2017
DOI: 10.1002/slct.201702052
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Electrochemical Behavior of Cytochrome c on Aqueous Solutions Containing Choline‐Based Room Temperature Ionic Liquids

Abstract: Ionic liquids have been attracting considerable interest in wide diverse fields, including biotechnology applications. Metalloproteins' stability in such media is still a controversial subject. Divergent reports on the metalloproteins' stability have been published, although hydrated ionic liquids seem more beneficial for achieving efficient redox transitions with the proteins' redox centers. In the present study the electrochemical behavior of Cyt c in three choline-based ionic liquids aqueous solutions, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Other works regarding A-ILCS of quaternary ammonium-based ILs have shown the stability and enhanced activity of Cytochrome c. For instance, Papadopoulou et al reported the stability and a 20-fold increase in the activity of Cytochrome c in [OHC 2 NH 3 ]­[HCO 2 ] (60% in water), resulting from the high “chaotropicity” of the cation. Bhakuni et al showed the thermal stability and packaging of Cytochrome c for a month, with a 1.5-fold rise in activity in an IL-based medium comprising [Cho]­[dhp] (50%) and synthetic crowding agents, like Fycol + ethylene glycol + sucrose (5%).…”
Section: Ionic Liquid-protein Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other works regarding A-ILCS of quaternary ammonium-based ILs have shown the stability and enhanced activity of Cytochrome c. For instance, Papadopoulou et al reported the stability and a 20-fold increase in the activity of Cytochrome c in [OHC 2 NH 3 ]­[HCO 2 ] (60% in water), resulting from the high “chaotropicity” of the cation. Bhakuni et al showed the thermal stability and packaging of Cytochrome c for a month, with a 1.5-fold rise in activity in an IL-based medium comprising [Cho]­[dhp] (50%) and synthetic crowding agents, like Fycol + ethylene glycol + sucrose (5%).…”
Section: Ionic Liquid-protein Systemsmentioning
confidence: 99%
“…Bhakuni et al showed the thermal stability and packaging of Cytochrome c for a month, with a 1.5-fold rise in activity in an IL-based medium comprising [Cho]­[dhp] (50%) and synthetic crowding agents, like Fycol + ethylene glycol + sucrose (5%). Matias et al reported the retention of intrinsic redox properties of Cytochrome c in an aqueous solution of [Cho]­[dhp] and [Cho]­[MES]. Still, with cholinium-based ILs, Bisht et al demonstrated the thermal and thermodynamic stability of Cytochrome in A-ILCS of [Cho]­[Glu]:water (50:50, w/w) under multiple stresses, such as temperature and H 2 O 2 .…”
Section: Ionic Liquid-protein Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionogels have also been studied as catalytic membranes by loading the material with various types of catalysts. Since some ILs work well in enhancing the activity and stability of enzymes [12,13], some ionogels are an attractive medium for biocatalysis, namely for building electrodes for enzymatic fuel cells or as biosensors [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bisht et al 30 concluded that choline acetate [Ch] + [Ac] − is the best stabilizer, while choline hydroxide [Ch] + [OH] − acts as the destabilizer for αchymotrypsin. On the other hand, Matias et al 31 observed no considerable changes in the redox behavior of cytochrome c (Cyt c) in [Ch] + [Dhp] − . Fujita et al 32 showed no Cyt c structural modification and maintained its activity when dissolved in the [Ch] + [Dhp] − .…”
Section: Introductionmentioning
confidence: 99%